Association of anti-phospholipid antibodies with connective tissue diseases - Reena Rai; T Swetha (Wolters Kluwer Medknow Publications, 2015)
Background: The antiphospholipid antibodies (APLA) are directed against phospholipids and their binding proteins and are frequently found in association with connective tissue disorders. Systemic lupus erythematoses (SLE) with APLA may cause a diagnostic dilemma as there are several manifestations like haemolytic anemia, thrombocytopenia, neurologic manifestations, leg ulcerations, serositis proteinuria which overlap in both these conditions. We conducted a study to find out the association of antiphospholipid antibodies with connective tissue diseases and compared the clinical and laboratory parameters between antiphoshpolipid antibody positive and antiphoshpolipid antibody negative group. Materials and Methods: This study was carried out in 102 patients diagnosed with connective tissue diseases. APLA testing was done at baseline and for those positive, the test was repeated after 12 weeks. Results: 14.7 % of patients with connective tissue diseases tissue had positive antiphoshpolipid antibodies. Positive antiphoshpolipid antibody was detected in 73.3% of patients with SLE group, 13.3% of patients with mixed connective tissue disease (MCTD) and 13.3% of patients with systemic sclerosis. APLA positivity was seen in SLE patients with leg ulcers (87.2%), neurologic manifestation (72.7%), hemolytic anemia (62.3%), thrombocytopenia (72.7%), serositis (27.8%) and proteinuria(19.6%). Conclusions: Antiphoshpolipid antibodies should be tested in all patients with connective tissue disease.